Possible Role of the Transglutaminases in the Pathogenesis of Neurodegenerative Diseases - Iannaccone, Martina; Titta, Federica; Marra, Fabiana; Gentile, Vittorio (Journal of Aging and Gerontology, 2013)
Transglutaminases are ubiquitous enzymes which catalyze posttranslational modifications of proteins. Recently, transglutaminase-catalyzed post-translational modifications of proteins have been shown to be involved in molecular mechanisms responsible for human diseases. Transglutaminase-catalyzed post-translational modifications of proteins have been hypothesized to be involved also in the pathogenetic mechanisms responsible for several human neurodegenerative diseases. Alzheimer’s disease and other neurodegenerative diseases, such as Parkinson’s disease, supranuclear palsy, Huntington’s disease, and other polyglutamine diseases, are characterized in part by aberrant cerebral transglutaminase activity and by increased cross-linked proteins in affected brains. This review focuses on the possible molecular mechanisms by which transglutaminase activity could be involved in the pathogenesis of Alzheimer’s disease and other neurodegenerative diseases, and on the possible therapeutic effects of selective transglutaminase inhibitors for the cure of patients with diseases characterized by aberrant transglutaminase activity.